Aljaraatheemu l imlaaqah - Capeci, Anne.; Speirs, John; Cole, Joanna (New York : Scholastic, 2006)
On a picnic in the park, Keesha and the other kids in Ms. Frizzle's class learn about the microbes all around them and soon find themselves pitted against the Giant Germ.
Text in Arabic.
3-6
Title supplied by OCLC WorldCat.
Translation of: Giant germ.
Keywords: Bacteria -- Fiction; Viruses -- Fiction; Arabic language materials; Bacteria -- Fiction; Viruses -- Fiction; Arabic language; Microrganisms -- Fiction